PERAN INTERNATIONAL LABOUR ORGANIZATION (ILO) DALAM MENGUPAYAKAN HAK PEKERJA PADA INDUSTRI GARMEN DI VIETNAM - Utami, Wahyuni; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
As one of the driving forces of the economy and the largest employer in Vietnam, the garment industry faces many issues related to the fulfillment of workers' rights. The International Labor Organization (ILO), a specialized agency of the United Nations (UN), plays a strategic role in promoting the protection of workers' rights in various countries, including Vietnam. This study aims to analyze how the ILO has worked to advance garment workers' rights in Vietnam during the period 2019-2023. The findings indicate that the ILO plays a role through the establishment of international labor standards, which influence policy implementation and support both the government and industry stakeholders. The Better Work Vietnam program is a concrete initiative that has successfully improved working conditions in many garment factories. Through training, support, and advocacy provided by Better Work, positive impacts have been observed on creating a dynamic and safe working environment for garment workers in Vietnam. The conclusion of this study is that the ILO plays a significant role, both directly and indirectly, in advocating for the rights of garment workers in Vietnam. The recommendations include the need for continued oversight efforts and for the ILO's initiatives in Vietnam to be adopted by other countries facing similar issues. Keywords: International Labour Organization, Garment Industry, Workers' Rights, International Organization.